Bioorthogonal supramolecular cell-conjugation for targeted hitchhiking drug delivery. (November 2020) - Gao, Cheng; Cheng, Qian; Wei, Jianwen; Sun, Chen; Lu, Siyu; Kwong, Cheryl H.T.; Lee, Simon M.Y.; Zhong, Zhiyuan; Wang, Ruibing
Graphical abstract: Abstract: Cells possess inherent advantages to facilitate targeted payload delivery. Current strategies to conjugate payload carriers to the surface of cells are either via covalent bonds that not only involve complicated synthetic process but also often impair cellular functions, or via biological ligand-receptor interactions that are only specific to particular types of cells. Herein, we report a facile, bioorthogonal supramolecular conjugation strategy to prepare targeted cell-hitchhiking delivery systems, mediated via artificial host–guest interactions between β-cyclodextrin and adamantane, respectively anchored (via insertion) on the surfaces of live cells and payload carriers. In a paw swelling inflammation mouse model, supramolecularly conjugated macrophage-carriers (either cell–cell or cell-nanoparticle systems) were efficiently delivered hand-in-hand to the swelling paw, driven by the inflammatory tropism of macrophage. Furthermore, in an acute lung inflammation model of mouse, supramolecular conjugation of peritoneal macrophage and quercetin-loaded liposomes significantly improved targeting efficiency of the liposomes, and effectively alleviated the lung inflammation through the anti-inflammatory and anti-oxidative effects of quercetin. The cell-friendly, facile, host–guest interactions mediated cellular conjugation may provide the very first general strategy for preparing various cell-hitchhiking delivery systems to meet the needs of diverse biomedical applications.